GENE EXPRESSION (International journal of medical sciences, 2026)
This article provides a comprehensive overview of gene expression, focusing on its molecular mechanisms, regulation, and biological significance. Gene expression is a multi-level process that determines how genetic information is translated into functional products, such as proteins and RNAs, essential for cellular development, differentiation, and adaptation. The article discusses transcriptional, post-transcriptional, translational, and post-translational regulatory mechanisms, as well as epigenetic modifications that influence gene activity. The relevance of studying gene expression in understanding disease development, including cancer and genetic disorders, is highlighted. Additionally, modern techniques such as RNA sequencing, microarrays, and computational analysis are reviewed for their roles in analyzing gene expression patterns and regulatory networks. The article emphasizes the applications of gene expression knowledge in medicine, biotechnology, and synthetic biology.